Sirtuins Link Inflammation and Metabolism - Vidula T. Vachharajani; Tiefu Liu; Xianfeng Wang; Jason J. Hoth; Barbara K. Yoza; Charles E. McCall (Journal of Immunology Research)
Sirtuins (SIRT), first discovered in yeast as NAD+ dependent epigenetic and metabolic regulators, have comparable activities in human physiology and disease. Mounting evidence supports that the seven-member mammalian sirtuin family (SIRT1–7) guard homeostasis by sensing bioenergy needs and responding by making alterations in the cell nutrients. Sirtuins play a critical role in restoring homeostasis during stress responses. Inflammation is designed to “defend and mend” against the invading organisms. Emerging evidence supports that metabolism and bioenergy reprogramming direct the sequential course of inflammation; failure of homeostasis retrieval results in many chronic and acute inflammatory diseases. Anabolic glycolysis quickly induced (compared to oxidative phosphorylation) for ROS and ATP generation is needed for immune activation to “defend” against invading microorganisms. Lipolysis/fatty acid oxidation, essential for cellular protection/hibernation and cell survival in order to “mend,” leads to immune repression. Acute/chronic inflammations are linked to altered glycolysis and fatty acid oxidation, at least in part, by NAD+ dependent function of sirtuins. Therapeutically targeting sirtuins may provide a new class of inflammation and immune regulators. This review discusses how sirtuins integrate metabolism, bioenergetics, and immunity during inflammation and how sirtuin-directed treatment improves outcome in chronic inflammatory diseases and in the extreme stress response of sepsis.